Quality of life in patients with brain tumors in the course of alpha therapy. Issue 5 (3rd September 2017) - Kamińska, Marta; Fersten, Ewa; Koziara, Henryk; Królicki, Bartosz
ABSTRACT: The aim of the study was to assess subjective quality of life in patients receiving alpha therapy for malignant tumors (glioblastoma multiforme, GBM) of the brain. No significant differences in self-assessed quality of life were found between GBM patients in the course of α-therapy and healthy controls, the two groups differed only as regards somatic symptoms. Moreover, the stronger the respondents' sense of self-efficacy, the higher their subjective quality of life. The findings may have practical implications for clinical psychology, namely, it seems worthwhile to build up the patient's sense of control of his own health.